High‐density genotyping of the A.E. Watkins Collection of hexaploid landraces identifies a large molecular diversity compared to elite bread wheat. Issue 1 (28th July 2017) - Winfield, Mark O.; Allen, Alexandra M.; Wilkinson, Paul A.; Burridge, Amanda J.; Barker, Gary L.A.; Coghill, Jane; Waterfall, Christy; Wingen, Luzie U.; Griffiths, Simon; Edwards, Keith J.
Summary: The importance of wheat as a food crop makes it a major target for agricultural improvements. As one of the most widely grown cereal grains, together with maize and rice, wheat is the leading provider of calories in the global diet, constituting 29% of global cereal production in 2015. In the last few decades, however, yields have plateaued, suggesting that the green revolution, at least for wheat, might have run its course and that new sources of genetic variation are urgently required. The overall aim of our work was to identify novel variation that may then be used to enable the breeding process. As landraces are a potential source of such diversity, here we have characterized the A.E. Watkins Collection alongside a collection of elite accessions using two complementary high‐density and high‐throughput genotyping platforms. While our results show the importance of using the appropriate SNP collection to compare diverse accessions, they also show that the Watkins Collection contains a substantial amount of novel genetic diversity which has either not been captured in current breeding programmes or which has been lost through previous selection pressures. As a consequence of our analysis, we have identified a number of accessions which carry an array of novel alleles along with a number of interesting chromosome rearrangements which confirm the variable nature of the wheat genome.